Seasonal health tracking of Australian Football League Women`s athletes - Otte, C. J.; Mantzioris, E.; Salagaras, B. S.; Hill, A. M. (Science and Medicine in Football, 2024)
Background: Studies evaluating the dietary intake of Australian Football League Women`s (AFLW) athletes are few and limited to the preseason. This prospective observational study aims to evaluate seasonal changes in dietary intake and health parameters of professional AFLW athletes. Methodology: Dietary intake (3-day weighed food records), body composition (bioelectrical impedance analysis, skinfolds), physical performance (global positioning system, GPS), and iron status (fasted blood sample) were assessed in 19 athletes (24 ± 5 years, 170 ± 6 cm, 22.8 ± 2.1 kg/m2) at three timepoints: start of preseason, end of preseason, and end of competition season. Sociodemographic information, sports nutrition knowledge (SNK), and risk of low energy availability (LEA) questionnaires were completed at the start of preseason. Results: Mean daily energy and carbohydrate (CHO) intakes were lower than recommendations across all seasons (p < 0.05). Mean daily CHO intake was highest at start of preseason (3.6 g/kg/day), decreased during preseason (3.1 g/day) and remained low during competition (3.2 g/day); >80% of players did not meet minimum recommendations at each timepoint (all, p < 0.05). The sum of seven skinfolds and fat mass (%) decreased during preseason (both, p < 0.05). Serum iron fell within recommended ranges for 95% of athletes at all timepoints. The total distance (m) and number of Very High Intensity (>21 km/h) efforts significantly increased across preseason and decreased during competition (all, p < 0.05). Nutrition knowledge was `poor`, and 42% of athletes were at risk of LEA. Conclusions: AFLW athletes do not meet energy and carbohydrate requirements across the preseason and competition seasons, which may impact health and performance if deficits are sustained.